O papel das assembleias para o funcionamento do estado republicano segundo Jean-Jacques Rousseau - Nunes, Elga Lustosa de Moura (2021)
To the philosopher Jean-Jacques Rousseau, the assemblies are an important institute available to the people and perform the fundamental attribution of giving movement to the State, that is, making it work. Considering that, firstly and briefly, we'll focus on the civil society's formation and on the principles that establish the republican State by the philosopher's vision. Afterwards, we'll evaluate the assembly's own acts, since the appropriate structuring of the meetings to how they fulfill the designated role of maintenance of republican order. We'll look for arguments related to this act on the philosopher's main political works, especially in The Social Contract, a document that presents the direct relationship between the State's organization and the assemblies, so that we can define its main characteristics and models presented by the Genevan. All this framework regarding the assemblies will contribute to the functioning of the republican State, as it'll be demonstrated. Rousseau proposes a new wave to political thinking in the eighteenth century, allocating to the people the central role of State's businesses. In this manner, we'll defend that the assemblies are needed instruments both to contribute to the institution of this new model, consolidated on the public's participation, and to give legal safety to decisions taken by the people, as they represent one valid instrument of the restriction of rulers' actions, through the accountability and the regularity of the assemblies. This piece of the political gear will serve as a stabilizing element and as a consolidation of the republican order. Following Rousseau's guidelines on the matter, we'll work on the citizen's character while performing this activity, since it'll be their responsibility to conduct the assembly for the destined purposes, having to exercise their participation in various moments: opining, deliberating, deciding and voting. We'll also discuss that this instrument, if badly used, can serve as reinforcement to political corruption.